An acute gastroenteritis outbreak caused by GII.17 norovirus in Jiangsu Province, China. (August 2016) - Shi, Chao; Feng, Wei-Hong; Shi, Ping; Ai, Jing; Guan, Hong-Xia; Sha, Dan; Geng, Qian; Mei, Jun; Chen, Shan-hui; Xiao, Yong; Qian, Yan-Hua
Highlights: A rare norovirus genotype GII.17 variant caused outbreaks at a high school in Wuxi, Jiangsu Province, China in the winter of 2014. The outbreak was caused by the first case, who was affected outside the school. The epidemic curve and epidemiological investigation indicated that this outbreak was a point source type initially, followed by secondary person-to-person transmission. The water cooler in the classroom increased the risk of cross-contamination. Summary: Noroviruses are a common cause of acute gastroenteritis around the world; however, reports of outbreaks caused by GII.17 norovirus are rare. An outbreak caused by GII.17 norovirus in a senior high school in Wuxi, Jiangsu Province, China is reported here. An epidemiological investigation, pathogen detection, and case–control study were performed. Epidemiological data combined with the epidemic curve indicated that this outbreak was a point source type initially, followed by secondary transmission. The first case was identified as most likely the source of the outbreak. Risk analysis showed exposure to patients and sharing a communal water cooler to be associated with the spread of infection. Sequence analysis of GII-positive samples confirmed that the norovirus GII.17 variant was the etiological agent of this outbreak.